Correlation between Students’ Reading Habit and Their Cross Cultural Understanding - Agustina Lestary; Ninuk Krismanti; Imam Hendra Saputra (UMBanjarmasin, 2020)
This study is conducted to describe the correlation between reading habit and cross cultural understanding. The subject of this study is students of English Department of STKIP PGRI Banjarmasin. The data are obtained through questionnaire, to find out students’ reading habit, and test, to measure students’ intercultural knowledge. SPSS is used to analyze the correlations between these two variables. The result of the test shows that most students make mistakes in answering the questions related to cultural knowledge. However, the reading habit is not the determinant factor of the test’s result. This means that there is no significant correlation between students’ reading habit and the cross cultural knowledge.